Planejamento integrado de filtros harmônicos e reguladores de tensão em sistemas de distribuição utilizando um algoritmo multiobjetivo - Santos, Felipe Santana (2017)
The increase in linear and non-linear loads experienced by Brazil in recent years has changed the way distribution networks are planned and Operated. In addition, the competitiveness of the market and the demand for the improvement in power quality indexes mean that current e orts are increasingly focused on areas such as voltage profile control and voltage harmonic distortion control. This work deals, exactly, with the Integrated control of voltage and harmonic voltage distortion (volt/thd) in distribution systems, within the scope of planning, through the insertion of passive harmonics filters and voltage regulators. To solve the problem in question, a multiobjective algorithm, the NSGA-II, is applied, since the presented problem can be treated as a combinatorial optimization problem. The power summation method is used as an alternative for the resolution of the load flow. While the current injection method is used as a calculation of the harmonic flow. The mathematical models of the network components were presented, taking into account the influence of frequency, in a detailed way. The proposed algorithm was applied in benchmark systems, a 34-bus and a 104-bus, the systems were simulated with and without the presence of the devices for comparison and validation of the results.